Pengaruh Latihan Plyometrics â€œDepth Jumpâ€ Terhadap Peningkatan Vertical Jump pada Atlit Bola Voli Putri Yunior di Klub Surakarta (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2008)
The Study of Plyometrics â€œDepth Jumpâ€ Exercise Effect on Increasing of vertical jump to junior woman volley ball athletes in vita club Surakarta Plyometrics â€œdepth jumpâ€ exercise effeect on increasing of vertical jump to junior woman volley ball athletes by active motor units, with muscle spindle stretch reflex respons. The aims of this research were exa-mining the research subject characteristic and vertical jump afte plyometrics â€œdepth jumpâ€ exercise. The method of this research was experiment of the same subject. The sampling was done in 2 time, before and after treatment (plyometrics â€œdepth jump exercise). Vertical jump was measured by jump in the wall with centimeter index. Statistic method used in this research wasÂ  paired t-tes. The result was a significant defference before and after treatment (p<0,05).There was significant influence between plyometrics â€œdepth jumpâ€ exercise toward vertical jump.Keywords: Plyometrics, Depth Jump, Vertical Jump